Hvad kan vi lære af Grønbech? - Bilde, Per (Religionsvidenskabeligt Tidsskrift, 1988)
Nogle grundlæggende religionsvidenskabelige metodeovervejelser. Vilhelm Grønbech (1873-1948) is so far the most important and well-known Danish historian of religion. In 1987, Professor J. Prytz-Johansen published a new book on Grønbech, and this is the immediate occasion for this article which surveys Grønbech’s life and works, and the secondary literature on Grønbech before and including Prytz-Johansen. Its primary aim, however, is to describe Grønbech’s “project” and religio-social “method” – these are unsatisfactorily treated by Prytz-Johansen – in order to reflect on their validity for us today. The conclusion is, primarily, that we from Grønbech may learn that also the science of religion is a public, cultural and political affair, and, consequently, that we as scholars need to become aware of this fact and of the responsebility vis à vis our society which follows from this fact. Secondly, we may learn from Grønbech’s peculiar “method” of “objective subjectivity” or “subjective objectivity” and from his “holistic” approach to religion. Further, we may learn something from his ideas or definition of religion. And finally, it would be fortunate if we today could learn a little from Grønbech’s beautiful and straightforward way of presenting his results to the public. Consequently, there are good reasons not to forget Grønbech either in Denmark or abroad.